2018
DOI: 10.26444/aaem/75544
|View full text |Cite
|
Sign up to set email alerts
|

Study on changing patterns of reproductive behaviours due to maternal features and place of residence in Poland during 1995–2014

Abstract: Introduction. The sharp decline in the total fertility rate in Poland coincided with broader socio-economic changes, which resulted in its reduction to the lowest level observed among the countries of Central and Eastern Europe. Objective. The aim of the study was to investigate and evaluate the changing patterns of reproductive behaviour in rural and urban areas, depending on the demographic and socio-economic features in Poland. Materials and method. Information about live births in Poland in the years 1995-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This study showed important implications for policy; that improving the macroeconomic situation appears to diminish mortality under 1 year of age in the EU. It is important in terms of low fertility levels and may be a guide in the decision-making process regarding the distribution of resources aimed at intervention for child health [ 36 ]. There is a need for government action to increase well-being and access to appropriate obstetric care.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed important implications for policy; that improving the macroeconomic situation appears to diminish mortality under 1 year of age in the EU. It is important in terms of low fertility levels and may be a guide in the decision-making process regarding the distribution of resources aimed at intervention for child health [ 36 ]. There is a need for government action to increase well-being and access to appropriate obstetric care.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty women, group 1 consisting of 29 pregnant and group 2 consisting of 21 non-pregnant women, took part in the study. All participating women were of reproductive age (non-pregnant: M age = 25; SD = 2; pregnant: M age = 30; SD = 4; Z= −4.33, p < 0.001), and the average age in group 1 was higher (as the postponement of childbirth until older age has been observed in Poland [30]). Taking into account the length of reproductive age (from 15 to 49 years [31]), the observed age difference between the groups can be regarded as of no clinical significance.…”
Section: Participantsmentioning
confidence: 99%
“…However, data on these relationships in Central and Eastern European countries are limited [9,10]. In countries such as Poland, where significant changes or second demographic transition coincide with political reforms during the last decades [11,12], the identification of birth weight-related factors can be interesting. The demographic crisis worsened as a result of reforms that improved education, widened access to higher education, and increased the professional activity of women.…”
Section: Introductionmentioning
confidence: 99%